2001
DOI: 10.1046/j.1365-2044.2001.01708-2.x
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of diaphragmatic paralysis following supraclavicular brachial plexus block and its effect on pulmonary function

Abstract: SummaryThis re-survey of neurosurgical centres was conducted to determine whether the publication of management guidelines has resulted in changes in the intensive care management of severely headinjured patients (defined as Glasgow Coma Score , 9) in the UK and Ireland. Results were compared with data collected from a similar survey conducted 2 years earlier. Almost 75% of centres monitor intracranial pressure in the majority of patients and 80% now set a target cerebral perfusion pressure of . 70 mmHg. The u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
52
2
7

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 106 publications
(64 citation statements)
references
References 17 publications
3
52
2
7
Order By: Relevance
“…This resulted in sudden onset of inspiratory stridor and severe respiratory distress. The concomitant phrenic nerve block, which can be anesthetized (36-67%) when a supraclavicular block is performed, might have further aggravated the patient's symptoms [2,3]. The onset time of inspiratory stridor in our patient coincided with the development of sensory loss and muscle weakness in the ipsilateral limb.…”
Section: Discussionmentioning
confidence: 79%
See 1 more Smart Citation
“…This resulted in sudden onset of inspiratory stridor and severe respiratory distress. The concomitant phrenic nerve block, which can be anesthetized (36-67%) when a supraclavicular block is performed, might have further aggravated the patient's symptoms [2,3]. The onset time of inspiratory stridor in our patient coincided with the development of sensory loss and muscle weakness in the ipsilateral limb.…”
Section: Discussionmentioning
confidence: 79%
“…Acute respiratory complications in the form of phrenic and recurrent laryngeal nerve (RLN) palsies have been reported but are usually of no or minimal clinical significance [2][3][4]. We encountered a case of severe respiratory distress after right-sided supraclavicular block in a patient with unrecognized pre-existing leftsided vocal cord palsy.…”
Section: Introductionmentioning
confidence: 98%
“…Their study showed the most common pattern of the phrenic nerve consists of phrenic nerve with single C3 and C4 rootles with an immeasurable C5 which was present in 26% of the necks. and post operative complications (MAK, 2001). Another set of our findings revealed some variations of the pericardium.…”
Section: Discussionmentioning
confidence: 90%
“…Interscalene block is commonly associated with decreased diaphragmatic motion and pulmonary function when tested by ultrasonography and spirometry, repectively. [9][10][11] The duration of diaphragmatic paralysis is variable, lasting from 75 min to four hours depending on the type of cervical block and whether epinephrine is used in combination with the local anesthetic. 8,12 Superficial cervical block, unlike the deep block, carries a low risk of complications related to nerve paralysis.…”
Section: Discussionmentioning
confidence: 99%